2023
DOI: 10.9734/ajaees/2023/v41i81992
|View full text |Cite
|
Sign up to set email alerts
|

Study of Gaps in Adoption of Improved Tasar Silkworm (Antheraea mylitta D) Rearing Technologies

Abstract: Maharashtra contributes paltry 0.76 per cent of the total production of tasar silk in the country, with 23 MT but the production of tasar silk in the state is found to be dwindling which might be due to the gaps in knowledge and adoption of improved tasar silkworm rearing technologies. Therefore, present investigation was undertaken to assess the gaps in adoption of tasar silkworm rearing technologies and constraints faced by the tasar farmers in adopting the recommended technologies. The study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…However, without adoption of those technologies by the tasar silkworm rearers will not make the state prosper. Gedam et al [11] in their study of adoption gaps of improved tasar silkworm rearing technology in Maharashtra have reported that the major gaps in adoption were seen the practices such as Integrated Pest Management for the control of gall disease (91.67%), application of Farm Yard Manure (FYM) or vermi-compost @4 kg/plant or 2kg/plans twice in a year (87.50%) and foliar spraying of 1.5% urea twice @ 15 days' interval before 30 days of rearing (78.33%) and these were ranked 1 st , 2 nd and 3 rd , respectively and the average gaps in adoption were to the tune of 52.71 per cent. More than 50 per cent gaps in adoption of the recommended technologies could be a major cause for the declining of the tasar silk production in the state.…”
Section: Introductionmentioning
confidence: 99%
“…However, without adoption of those technologies by the tasar silkworm rearers will not make the state prosper. Gedam et al [11] in their study of adoption gaps of improved tasar silkworm rearing technology in Maharashtra have reported that the major gaps in adoption were seen the practices such as Integrated Pest Management for the control of gall disease (91.67%), application of Farm Yard Manure (FYM) or vermi-compost @4 kg/plant or 2kg/plans twice in a year (87.50%) and foliar spraying of 1.5% urea twice @ 15 days' interval before 30 days of rearing (78.33%) and these were ranked 1 st , 2 nd and 3 rd , respectively and the average gaps in adoption were to the tune of 52.71 per cent. More than 50 per cent gaps in adoption of the recommended technologies could be a major cause for the declining of the tasar silk production in the state.…”
Section: Introductionmentioning
confidence: 99%